Growth of Gracilaria sp. in Monoculture and Polyculture System with Milkfish (Chanos chanos Forsk) in Traditional Ponds, Brebes Regency, Central Java - Rahmawati, Vira Rizqi; Rejeki, Sri; Amalia, Rosa; Widowati, Lestari Lakhsmi; Ariyati, Restiana Wisnu; Nauta, Reinier; Lansbergen, Romi (Jurnal Kelautan Tropis, 2024)
Gracilaria sp. has a high economic value, which can be cultivated in monoculture or polyculture with other cultivars, such as milkfish (Chanos chanos Forsk). Polyculture of Gracilaria sp. with milkfish can increase the growth of Gracilaria sp. because the metabolic products of milkfish are helpful as a source of nutrients for Gracilaria sp. This study aimed to (1) examine the effect of Gracilaria sp. cultivation in monoculture and polyculture with milkfish on the growth of Gracilaria sp. and (2) the nutrient content of the water. This study used an experimental method with two treatments and three replications using six (6) earth ponds: Gracilaria sp. monoculture and polyculture with milkfish. Growth and nutrient content (nitrate and phosphate) data were analyzed using a t-test. The results of the study showed that the growth of Gracilaria sp. polyculture with milkfish provided absolute growth of 3615.89 ± 330.84 g; Relative Growth Rate (RGR) 180.79 ± 16.54 %; and Specific Growth Rate (SGR) 2.29 ± 0.13 %/day were significantly higher, compared with the growth of Gracilaria sp. monoculture. Monoculture Gracilaria sp showed absolute growth of 1912.71 ± 386.94 g; RGR 95.64 ± 19.35 %; and SGR 1.48 ± 0.22 %.day-1. Nutrient content in polyculture pond waters revealed nitrate 1.08 ± 0.09 mg.L-1 and phosphate 0.18 ± 0.04 mg.L-1 were significantly higher compared to nutrient content in monoculture pond waters which were nitrate 0.71 ± 0.22 mg.L-1 and 0.07 ± 0.04 mg.L-1. Polyculture Gracilaria and seaweed provide higher production due to the enrichment from nutrient content.